Difficulties encountered by grade-10 students at Truong Dinh upper secondary school in learning writing skill with the new textbook Tieng Anh 10 - Kiều, Thu Hiền (University of Foreign Languages and International Studie, 2017)
Chapter I (Literature review): presents the theoretical background of the study, which summarizes some views on definitions of writing, differences between written language and spoken language, roles of writing in second language learning, approaches to the teaching of writing in ESL classes and what makes writing difficult to acquire. Chapter II (The study) includes the context of the study, the research questions, the participants, data collection methods, procedures, analysis and discussion. The analysis and discussion part discusses and analyses difficulties encountered by grade-10 students at Truong Dinh Upper secondary school in learning writing skill with the new textbook Tieng Anh 10. Chapter III (Solutions) suggests some relevant measures to deal with students' problems and learn writing skill more effectively.